Anatomy of the Middle Meningeal Artery - Marco Aurélio Ferrari Sant'Anna (Thieme Revinter Publicações Ltda., 2021)
Introduction The middle meningeal artery (MMA) is an important artery in neurosurgery. As the largest branch of the maxillary artery, it provides nutrition to the meninges and to the frontal and parietal regions. Diseases, including dural arteriovenous fistula (DAVF), pseudoaneurysm, true aneurysm, traumatic arteriovenous fistula (TAVF), Moya-Moya disease (MMD), recurrent chronic subdural hematoma (CSDH), migraine, and meningioma, may be related to the MMA. The aim of the present study is to describe the anatomy of the MMA and to correlate it with brain diseases. Methods A literature review was performed using the PubMed, Scielo, Scientific Direct, Ebsco, LILACS, TripDataBase and Cochrane databases, with the following descriptors: neurosurgery, neuroanatomy, meninges and blood supply. Discussion The MMA is embedded in a cranial groove, and traumatic or iatrogenic factors can result in MMA-associated pseudoaneurysms or arteriovenous fistulas (AVFs). In hemodynamic stress, true aneurysms can develop. Arteriovenous fistulas, pseudoaneurysms, and true aneurysms can be effectively treated by endovascular or surgical removal. In MMD, the MMA plays a role in the development and in the improvement of collateral circulation. Finally, in cases of CSDH, when standard surgery and drainage fail, MMA embolization can constitute a great alternative. Conclusion The MMA is a relevant structure for the understanding of neurosurgical diseases. In conclusion, every neurosurgeon must know the anatomy of the MMA sufficiently to correlate it with the diagnosed pathology, thus obtaining treatment effectiveness and preventing brain lesion.